(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Political, socio-economic consequences of the inter-ethnic conflict in the southern region of Kyrgyzstan. Theoretical foundations. Socio-economic, cultural-linguistic, regional-status and separatist interests. Study of the causes of interethnic conflicts in 1990 and 2010 by comparative methods. Percentage indicators of representatives of Kyrgyz and Uzbek nationalities living in the city. The reason is the influx of Kyrgyz youth to the city. Statistical indicators of the minimum amount of funds necessary for living, compared to labor income. low salary, low standard of living. One of the main factors directly contributing to the tragic incident in Osh is the unresolved housing issue. Increased political activity of people with the democratic process. Formation of informal «Osh region» and separatist organization «Adolat». High requirements. The beginning of the conflict. Conflict between two sides. Hod blood history. Loss of human resources and economic suffering. Consequences of the conflict. Nakazat party workers. The activity of party bodies is aimed at liquidating the resulting conflict.